Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)